2016
DOI: 10.1016/j.jvoice.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Electroglottographic Signal and Vocal Fold Contact Area

Abstract: Overall, there was a better agreement between VFCA and the EGG waveform in the decontacting phase than in the contacting phase. Disagreements may be caused by nonuniform tissue conductance properties, electrode placement, and electroglottograph hardware circuitry. Pending further research, the EGG waveform may be a reasonable first approximation to change in medial contact area between the VFs during phonation. However, any quantitative and statistical data derived from EGG should be interpreted cautiously, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…The electroglottographic (EGG) signal is proportional to changes of the relative vocal fold contact area during vocal fold vibration [59]. It is thus well suited for documenting the vocal fold oscillatory effects of any potentially occurring register transitions or instabilities during the examined pitch glides.…”
Section: Methodsmentioning
confidence: 99%
“…The electroglottographic (EGG) signal is proportional to changes of the relative vocal fold contact area during vocal fold vibration [59]. It is thus well suited for documenting the vocal fold oscillatory effects of any potentially occurring register transitions or instabilities during the examined pitch glides.…”
Section: Methodsmentioning
confidence: 99%
“…A high-frequency, low-voltage current is passed between two electrodes placed on either side of the thyroid cartilage at the level of the vocal folds. Changes in the vocal fold contact area (VFCA) during vocal fold vibration result in admittance variations, and the resulting EGG signal is proportional to the relative VFCA (Hampala et al, 2016).…”
Section: Electroglottography: Methodsmentioning
confidence: 99%
“…Scherer et al 12 employed a mechanically-driven contact-decontact model in excised canine hemilarynges to show that an approximately linear relationship between the normalized EGG value and VFCA was obtained in some cases. Hampala et al 13 more recently used an excised deer hemilarynx phonation model to show that the agreement between EGG and VFCA was better in the decontacting phase than in the contacting phase. Other studies suggested that EGG pulse width measures relate to the degree of vocal fold medial compression.…”
Section: Introductionmentioning
confidence: 99%